Pain & gain [videorecording (Blu-Ray + DVD)] - Harris, Ed, 1950-; Wahlberg, Mark, 1971-; Johnson, Dwayne, 1972-; Shalhoub, Tony, 1953-; Jeong, Ken, 1969-; Corddry, Rob; Mackie, Anthony, 1978-; Wilson, Rebel; De Line, Donald; Bay, Michael, 1964-; Bay, Michael, 1964-; Bryce, Ian; et al. (Paramount, 2013)
When an ambitious group of personal trainers go after the American dream, they get caught up in a criminal enterprise that goes horribly wrong. Now, living large will take everything they've got.